Державна реєстрація права приватної власності фізичних осіб на житловий будинок та квартиру: порядок та правова природа - Копилова, Ж. В.; Копылова, Ж. В.; Kopilova, J. (Одеса : Юрид. л-ра, 2012)
In the article considered questions regarding order and legal foundation of state registration property rights of physical persons on to house and apartment. Made conclusion that by state registration of property rights of the physical persons dwelling house and apartment. Submitted to provide in valid Housing Code of USSR at 1983 year — Article: «Acquisition proprietary of dwelling*.
Копилова Ж. В. Державна реєстрація права приватної власності фізичних осіб на житловий будинок та квартиру: порядок та правова природа / Ж. В. Копилова // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю .П. Аленін [та ін.] ;МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Вип. 67. - С. 431-440.
Keywords: державна реєстрація речових прав на нерухоме майно; Державний реєстр речових прав на нерухоме майно; житловий будинок; квартира; правоустановчі документи; право приватної власності; государственная регистрация вещных прав на недвижимое имущество; Государственный реестр вещных прав на недвижимое имущество; жилой дом; квартира; правоустанавливающие документы; право частной собственности; state registration law of property on immovable estate; State register law of property immovable estate; dwelling house; apartment; establishing documents of rights; law of private property